Correspondance formelle dans le roman L’étranger et Orang Asing - Linggar Okta Wijayanti; Dies Oktavia Dwi Astuti (Universitas Negeri Semarang, 2025)
We chose to compare formal correspondence in the novels L'étranger and Orang Asing to identify similarities in form and meaning between the two books. This research aims to describe the formal correspondence in the novels L'étranger and Orang Asing. This research is qualitative descriptive research. The theory used to analyse the data is Catford's theory of formal correspondence. The data sources for this research are the novels L'étranger in French and Orang Asing in Indonesian. The data for this research consist of propositions that exhibit formal and semantic correspondences in the novels L'étranger and Orang Asing. The research results show that there are 24 propositions with formal correspondences. The formal correspondence is based on units of 24 propositions, formal correspondence based on word classes of 16 propositions, and formal correspondence based on structures of 5 propositions. The SL and TL propositions share a connection in meaning, conveying the same message.